(untitled) (Studia Prawnicze / The Legal Studies, 2007)
Znaczne uproszczenia proceduralne w zakresie udzielania zamówień publicznych w trybie zapytania o cenę sprawiają, że jest to w praktyce jeden z najczęściej stosowanych sposobów zamawiania sprzętu, materiałów oraz innych dostaw i usług przez jednostki sektora finansów publicznych, zwłaszcza przez urzędy, szkoły, instytucje kultury, placówki publicznej służby zdrowia i pomocy społecznej. Z naturalnych względów regulacja prawna tego rodzaju postępowania rzutuje wyraźnie także na interesy przedsiębiorców, zwłaszcza drobnych dostawców i wykonawców świadczeń zamawianych na cele publiczne. Question of price procedurę it is a kind of auction which is open to selected persons. This procedurę is started by inviting chosen contactors to submitting offers. It is not covered by European Law. It can be used only while ordering small deliveries or services, the amount of which do not exceed 137 thousand EUR. Person who orders, invites enough contactors to allow real competition, but not less that 5 persons. A threat to fair competition is obvious. Condition of ordering together with bidder’s reąuirements, but also essential provisions of finał contract are delivered in advance along with invitation. Procedurę is efficient on the condition that there will come at least 2 proper offers. Choosing and accepting the most favorable offer leads to concluding temporary and preliminary contract, which creates an obligation to sign public procurement contract. This contract should be concluded in a period not shorter than 7 days (protests), but no latter than all other offers will expire. Because if the the winner evaded contract, person who orders will have to chose next offer, unless there is a basis to annul the whole procedurę.